Prevalence of Sarcoptes scabiei, clinical sings and some hematologi-cal parameters in sheep in Bqubah city, Diyala province, Iraq - jassam, Ahmed talib; Hussein, Raad Mahmood; Hussein, Haleem hamza (Diyala Journal for Veterinary Sciences, 2023)
Scabies is one of the important neglected tropical skin diseases which caused by the parasitic mite Sarcoptes scabiei. This study was designed to investigate the prevalence and clinical some hematological alterations induced by mite infestation in sheep at in the Baqubah city, Iraq. Be-side the effects of age, gender and Season. A random selection of total sheep flocks 681 includ-ed 266 males and 415 females. Samples were collected from November 2021 to March 2022. Skin scrapings were collected from sheep clinically showed lesion of mange for diagnosis the Sarcoptes scabiei. Clinical and hematological parameters were adopted in this study. Results showed that the main clinical signs, wool loss, crusts, pityriasis, pustules,Significant increase in the respiratory and heart rate. with an infection rate of 8% distributed as 266 male with 19(3%) infested and 415 female with 37(5%) , prevalence of the infestation was highest in sheep under one year old compared with sheep more than one years old . The prevalence of the infestation was highest in wintertime January and February 12%, 18% respectively. Hematological parame-ters in sheep infested with S. scabiei species were significant differs in values of total red blood cells (RBCs ×106 /l), white blood cell (WBC ×106 /μl), hemoglobin concentration (Hb g/dl) , Although the packed cell volume (PCV %) in infested sheep was lower than non- infested ones but it did not differ. In conclusion, the present study has shown that mange is still constitutes a notable problem, even with a limited percentage in Baqubah city, Iraq. Infestation with Sar-coptes scabiei does not affected by gender. Age under than one year is more susceptible to infes-tation. And the more infestation sheep with poor condition and malnutrition and bad manage-ment from owner.